UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MAHASISWA MELALUI PENERAPAN MODEL PEMBELAJARAN INKUIRI PADA MATA KULIAH KONSEP DASAR IPA 2 DI PROGRAM STUDI PENDIDIKAN GURU SEKOLAH DASARTAHUN AKADEMIK 2013/2014 - Mahmud Alpusari (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2014)
In line with the competency-based curriculum at the University of Riau, efforts to improve learning in the Basic Concepts of Science 2 course emphasize students’ conceptual understanding of matter through learning activities grounded in scientific inquiry. This study employed classroom action research conducted in two cycles involving 55 third-semester students of the PGSD JIP Program at the University of Riau during the odd semester of the 2013/2014 academic year. The findings indicate that the implementation of the inquiry learning model improved both student activity and learning outcomes. In the first cycle, most learning activities were categorized as good, although activities I and II remained in the fair category. In the second cycle, students’ activity reached the good category in the first and fourth activities and the very good category in the second, third, fifth, and sixth activities. Students’ learning outcomes also showed improvement, with the average score increasing from 65.45 in the pre-test to 77.00 in Daily Test I and 77.45 in Daily Test II. The improvement from the initial data to the first cycle was 11.55 points, while the increase from the initial data to the second cycle reached 12 points. Overall, the enhancement of students’ learning outcomes was achieved because inquiry-based learning encourages active, student-centered learning by presenting problems, engaging students in simple experiments using appropriate tools and materials, analyzing data, preparing reports, and communicating observational results based on scientific concepts and principles learned.